Coffee components and cardiovascular risk: beneficial and detrimental effects. (December 2014) - Godos, Justyna; Pluchinotta, Francesca Romana; Marventano, Stefano; Buscemi, Silvio; Li Volti, Giovanni; Galvano, Fabio; Grosso, Giuseppe
Abstract Coffee consists of several biological active compounds, such as caffeine, diterpenes, chlorogenic acids, and melanoidins, which may affect human health. The intake of each compound depends on the variety of coffee species, roasting degree, type of brewing method and serving size. The bioavailability and the distribution of each compound and its metabolites also contribute to coffee mechanisms of action. The health benefits of coffee consumption regarding cardiovascular system and metabolism mostly depend on its antioxidant compounds. In contrast, diterpenes and caffeine may produce harmful effects by raising lipid fraction and affecting endothelial function, respectively. Studying the mechanism of action of coffee components may help understanding weather coffee's impact on health is beneficial or hazardous. In this article, we reviewed the available information about coffee compounds and their mechanism of action. Furthermore, benefits and risks for cardiovascular system associated with coffee consumption will be discussed.